Perlindungan Saham Minoritas PT (Persero) Dalam Pembentukan Anak Perusahaan BUMN - Hamanda Tiara Emanuella (MLJ Merdeka Law Journal, 2022)
BUMN (Persero) is regulated in Law Number 19 of 2003 concerning BUMN. In practice BUMN (Persero) is subject to Law Number 40 of 2007, which regulates the rights of shareholders. However, when the Persero BUMN established a subsidiary based on a GMS decision, where the majority shareholder sided with it, which made the rights of minority shareholders neglected. The aim of the research is to analyze the pattern of protection for minority shareholders of PT (Persero) according to the corporate legal system and legal remedies for minority shareholders in protecting their rights to action. This research is normative legal research with the nature of descriptive analysis research. The results of the study are that legal protection for BUMN minority shareholders is regulated in the BUMN Law and the Limited Liability Company Law, but there are rights of minority shareholders which are only fulfilled if they receive support from the majority shareholders, so that the sense of justice for minority shareholders not protected, but there are efforts to resolve disputes that can be pursued both through litigation and non-litigation, especially Unlawful Acts (1365 BW) with the mechanism stipulated in the Company Law.DOI: https://doi.org/10.26905/mlj.v3i1.7930